A comprehensive review on alpha-lipoic acid delivery by nanoparticles - Navid Mosallaei; Amirhossein Malaekeh-Nikouei; Setayesh Sarraf Shirazi; Javad Behmadi; Bizhan Malaekeh-Nikouei (BioImpacts)
Alpha-lipoic acid (ALA) has garnered significant attention for its potential therapeutic benefits across a wide spectrum of health conditions. Despite its remarkable antioxidant properties, ALA is hindered by challenges such as low bioavailability, short half-life, and unpleasant odor. To overcome these limitations and enhance ALA's therapeutic efficacy, various nanoparticulate drug delivery systems have been explored. This comprehensive review evaluates the application of different nanoparticulate carriers, including lipid-based nanoparticles (solid lipid nanoparticles, niosomes, liposomes, nanostructured lipid carriers (NLCs), and micelles), nanoemulsions, polymeric nanoparticles (nanocapsules, PEGylated nanoparticles, and polycaprolactone nanoparticles), films, nanofibers, and gold nanoparticles, for ALA delivery. Each nanoparticulate system offers unique advantages, such as improved stability, sustained release, enhanced bioavailability, and targeted delivery. For example, ALA-loaded SLNs demonstrated benefits for skin care products and skin rejuvenation. ALA encapsulated in niosomes showed potential for treating cerebral ischemia, a condition largely linked to stroke. ALA-loaded cationic nanoemulsions showed promise for ophthalmic applications, reducing vascular injuries, and corneal disorders. Coating liposomes with chitosan further enhanced stability and performance, promoting drug absorption through the skin. This review provides a comprehensive overview of the advancements in nanoparticulate delivery systems for ALA, highlighting their potential to overcome the limitations of ALA administration and significantly enhance its therapeutic effectiveness. These innovative approaches hold promise for the development of improved ALA-based treatments across a broad spectrum of health conditions.